تأثیر استخدام شبكات التواصل الاجتماعي في الترویج للحظائر السیاحیة بولایة تیسمسیلت - لجلط , إبراهیم (Finance and Business Economies Review, 2018)
The study highblited the importance of the using social networks as a modern style in promoting the tourist serveces and tourist bans that are in the local places of tissemsilt, especially under the shade of rapid Technological devlopment, And to achieve that,it is procedured a study for 92 tourists male and femal who com to the national ban,ELMEDDAD ,AIN ANTER ,WILAYA OF TISSEMSILT.For this , a questionnaire is desigend to easure all the variables of this study ,commponetof 20 paragraphe So ,there is the verification of the semantis of validity and reliability rates.and for that,it twas used the computational averages,standasdeviations, the exam of bending, analusis of variance for answing all the question of the study and the test of its hypothesis. By the end ,this study reached to prove the effectiveness of using the social networks in tourism promotion of these bans.especially,the payes of facebook,youtube . After the finding , this study provided a set of recommendations such as :- the need to include all resident, enterprises of the tourist service,from Hotels ,tourist agencies and local adminstration on the pages in communication network to promote the tourist services and attract a large number of tourists